Odpowiedzi

2010-02-11T19:52:39+01:00
A) x+y=9 | *2
x-y=3 |*2
2x+2y=18
2x-2y=6
4x=24
x=6



D) x+4y=11 |*(-2)
2x+5y=10
-2x-8y=-22
2x+5y=10
-3y=-12 | :(-3)
y=4


C)
3x+2y=5 | :(-1)
2x=2y=2
-3x-2y=-5
2x+2y=2
-x=-3 |:(-1)
x=3



B)
3x+2y=2
-3x+y=10
3y=12
y=4
2010-02-11T20:00:16+01:00
A) x+y=9
x-y=3
2x=12/2
x=6

x + y=9
6+y =9
y=3

b) 3x+2y=2
-3x+y=10
3y=12/3
y=4

3x+8=2
3x=-6/3
x=-2
c)
3x+2y=5
2x+2y=2/*(-1)
3x+2y=5
-2x-2y=-2
x=3

9+2y=5
2y=-4
y=-2
d)
x+4y=11/*-2
2x+5y=10
-2x-8y=-22
2x+5y=10
-3y=-12/-3
y=4
2x+20=10
2x=-10/2
x=-5